Analysis of the milk supply chain of livestock farmer groups in Gunung Pati District, Semarang Regency - Aryani, Yovita; Putra, Daniel Pratama; Sijabat, Widia Novita; Ayu Christa, Audinta Mega; Priyanto, Agus (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2024)
The aim of this research is to determine the supply chain system, margins and marketing efficiency of dairy cow’s milk in Gunung Pati. This research was conducted in February-March 2024. The location of this research was determined purposively with the consideration that Gunung Pati District is a dairy cattle business center with great potential. The respondents in this study were the entire population of the three largest Farmer’s Groups (KTT) in Gunung Pati District, namely 68 dairy farmers consisting of KTT Rejeki Lumintu, KTT Sido Makmur and KTT Rukun Makmur. This research analysis method is descriptive in nature to describe the location and type of marketing channels. The results of the research show that the marketing margin and marketing efficiency it is good, this can be seen from farmers who get more than 50% of the profit, so the farmer’s profits are quite large.